Technology and Labor: Beyond the Promise of Efficiency (GESTIÓN Y TENDENCIAS, 2025)
This paper challenges the dominant narrative that treats technology as a neutral force driven solely by efficiency and productivity. Drawing on critical labor studies and on the work of Harvey and Braverman, the authors argue that technological innovation, including Artificial Intelligence, is intrinsically shaped by power relations and capital accumulation strategies. The analysis suggests that the primary function of these technologies is often to reorganize labor processes in order to reinforce managerial control and reduce worker autonomy, rather than simply to improve technical output. The text discusses how algorithmic management renders control invisible yet constant, leading to the precarization and deskilling of work. It closes with a call for the democratization of technological development and for regulation ensuring that digital tools foster human emancipation rather than subordination.
Keywords: algorithmic management; labor process; technological determinism; artificial intelligence; worker autonomy